The Triple “S” Impact of COVID-19: Nationwide Evidence of the Impact of the Stress Associated With Restrictive Measures on Substance Use, Sleep, and Social Connectedness in Qatar - Muna Abed Alah (18171346) (2023)
Objectives Countries worldwide implemented social and movement restrictions to contain the spread of coronavirus disease 2019 (COVID-19). Unfortunately, such restrictions have adversely impacted people’s lifestyles. The goal of this study was to assess the impact of COVID-19-related restrictive measures on substance use, sleep, and social connectedness in Qatar’s population. Methods A web-based survey was conducted between January 2021 and February 2021 targeting adults ≥18 years of age who were residing in Qatar between March and August 2020. Results A total of 1408 participants completed the survey. Of tobacco users in our sample, 36% reported increased tobacco use since the start of home confinement, while 41.6% of alcohol users reported decreased alcohol use. Concerning sleep, 46.1% reported an increase in average sleep duration per day (0.77 h mean increase, 95% CI: 0.66-0.88, P<0.001), and a third of participants reported poorer sleep quality. Of the participants, 39.6% felt socially disconnected. Perceived stress was found to be an independent predictor for increased use of tobacco, deterioration in sleep quality, and increased sleep duration during home confinement. Conclusions Restrictive measures related to COVID-19 resulted in both positive and negative impacts on the lifestyle of Qatar’s population. Emphasis should be placed on encouraging people to adopt healthy strategies for coping with various stressors that arise during future home confinement measures. It is also necessary to address the persistence of adverse consequences in the postpandemic era. Other Information Published in: Journal of Psychiatric Practice License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1097/pra.0000000000000737